PANDANGAN MASYARAKAT KOTA BANDUNG TERHADAP BANGUNAN CAGAR BUDAYA - Oesman, Yevis Marty; Oesman, Ida Farida (Strategic : Jurnal Pendidikan Manajemen Bisnis, 2016)
Balai Pertemuan Bumi Sangkuriang is one heritage building  in Bandung. However, its existence as a Heritage Building is still less known by the public in society Bandung. The attitude of the people of Bandung to Balai Pertemuan Bumi Sangkuriang just a meeting place that can only be visited by people of Bandung that are members of the society. This study aims to determine the attitude of the people of Bandung to the existence of Balai Pertemuan Bumi Sangkuriang as a heritage building. This study took a sample of 100 respondents by job. Data were processed using simple regression models.The results showed a significant influence on the attitude of the people in Bandung against BPBS Building existence as a Heritage Building. Perceptions of Attitudes Bandung society to Buildings BPBS rated Good. Similarly, public assessment of the existence of the building BPBS Bandung as a Heritage Building also rated Good.A good assessment of the attitude of the people of Bandung to the existence BPBS building as a heritage building, but managers still need to increase efforts to inform BPBS building as one of the heritage building in the city of Bandung. Keywords: Heritage building  , Attitude